Effects of high voice reading in reading understanding of primary students (Encuentros, 2017)
This research aimed to study the effects of reading aloud at the level of reading comprehension in elementary school students. The quantitative approach was assumed with a type of explanatory study under a quasi-experimental design with prebrand-posttest in a single experimental group. The sample was represented by a total of 33 students, after meeting criteria of inclusion and exclusion, they were applied the reading comprehension test of Progressive Linguistic Complexity (CLP), by Alliende, Condemarín, and Milicic, (1991). After the application, the strategy of the reading program in voice was executed in a period of time of 4 months. The analysis of the results was performed with the statistical package SPSS version 22 with the application of non-parametric statistics, since the sample did not present a normal distribution, so the Wilcoxon test was used, with a level of significance of 0.05. The results showed that students after application of the program significantly improved levels literal (p: 000) and inferential (p: 0.014 and p: 0.001). However for the critical textual level (p: 0.485 and p: 0.034) there is no statistical significance. It is concluded that levels of reading comprehension can improve with the intervention of reading aloud at their literal and inferential levels and it is corroborated that as one moves to another level of reading, the complexity is greater and to reach it is required Greater work and time.